2023
DOI: 10.1108/pr-11-2022-0832
|View full text |Cite
|
Sign up to set email alerts
|

Bots for mental health: the boundaries of human and technology agencies for enabling mental well-being within organizations

Debolina Dutta,
Sushanta Kumar Mishra

Abstract: PurposeThe importance of mental wellbeing and the need for organizations to address it is increasing in the post-pandemic context. Although Artificial Intelligence (AI) is increasingly being adopted in HRM functions, its adoption and utility for enabling mental wellbeing is limited. Building on the Open System Theory (OST) and adopting the technology-in-practice lens, the authors examined the roles of human and technology agencies in enabling mental wellbeing.Design/methodology/approachThe study was conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 52 publications
0
0
0
Order By: Relevance
“…government, industry associations and unions) and internal stakeholders could promote or impair employee mental health. A contextualized perspective is also reflected in other papers which investigated how technological advancement (in the external context) can bring positive implications for HRM in managing mental health issues, through the adoption of AI-based chatbots (Dutta and Mishra, 2024) and HR analytics (Lathabhavan, 2024), and in papers that tap into changing work practices as a result of COVID-19 (Silva, 2024; Wu et al , 2024). As context plays a crucial role in HRM strategy and implementation (e.g.…”
Section: Concluding Remarks and Future Research On Hrm And Mental Healthmentioning
confidence: 99%
See 4 more Smart Citations
“…government, industry associations and unions) and internal stakeholders could promote or impair employee mental health. A contextualized perspective is also reflected in other papers which investigated how technological advancement (in the external context) can bring positive implications for HRM in managing mental health issues, through the adoption of AI-based chatbots (Dutta and Mishra, 2024) and HR analytics (Lathabhavan, 2024), and in papers that tap into changing work practices as a result of COVID-19 (Silva, 2024; Wu et al , 2024). As context plays a crucial role in HRM strategy and implementation (e.g.…”
Section: Concluding Remarks and Future Research On Hrm And Mental Healthmentioning
confidence: 99%
“…Lathabhavan (2024), published in this special issue, reported that HR analytics improved organizations' evidence-based management and supported the implementation of mental health support practices. Another paper published in this special issue by Dutta et al (2024) demonstrated that integrating HRM and AI enhanced the management of employee mental health and well-being (e.g. use of AI chatbots to identify mental health challenges among workers).…”
Section: Human Resource Management and Mental Healthmentioning
confidence: 99%
See 3 more Smart Citations